KUALITAS LKPD ELEKTRONIK BERBASIS KETERAMPILAN BERPIKIR KRITIS PADA KONSEP EKOLOGI JENJANG SMA - Eka Nur Wahyuni; Muhammad Zaini; Amalia Rezeki (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
The world of education in the 21st century must produce a generation that is skilled in the application of technology and capable of critical thinking. Electronic Student Worksheets with indicators of critical thinking skills are present and have become an innovation of learning tools that were previously in print form to digital form. The goal of this research is to describe the practicality and effectiveness of the electronic LKPD expectations on the concept of Ecology. The Tessmer design is used in the research method, which includes: 1) expert review; 2) one-on-one evaluation; and 3) small group evaluation. The validation subjects were three experts; the individual test subjects were three class X high school students; and the small group test subjects were four class X high school students. The information gathered came from research instruments in the form of an assessment sheet for the practicality and effectiveness of expectations. Based on student responses, this research shows that the practical results of the electronic LKPD expectations are in a very good category, and the results of the effectiveness of expectations are in a very good category (covering interpretation, analysis, evaluation, inference, explanation, and self-regulation skills) based on the critical thinking skills assessment of students working on electronic LKPD.